Health Education Media â€œSmart with Your Foodsâ€ Increasing Selection of Foods Knowledge for Elementary School Students - Patriasih, Rita (INVOTEC, 2017)
The importance of the application of healthy behaviors in elementary schools need serious attention. Results of a preliminary study revealed the low student behavior, especially on the selection of healthy foods. Efforts to do one of them by conveying this information by using the right media health education. This study aimed to increase the knowledge of elementary school students through health education media "Smart with Your Foods". Implementation has been performed using a quasi-experimental design with non-equivalent control group pretest-posttest design. Research subjects are elementary school students. Respondents were divided into the experimental class and control class. This research reveals that "Smart with Your Foods" media effectively to enhance students' knowledge about the selection of healthy foods. Conclusion: This media is effective in improving the selection of foods knowledge for elementary school students